A COMPARETIVE ANALYSIS OF AERODYNAMIC CHARECTERISTICS OF A VERTICAL AXIS VANE TYPE WIND TURBINE OVER EVEN AND ODD NUMBER OF BLADES (Journal of Mechanical Engineering, 2015)
This paper reports on the experimental investigation of the aerodynamic effects on even and odd number bladed vertical axis vane type rotor. The experiment was conducted with the help of a subsonic wind tunnel together with the experimental set-up of the vane type rotor and a spring balance. To ensure a Reynolds number independent approach, different stream flow was maintained. The flow velocities varied from 5 m/s to 9 m/s covering the Reynolds number from 0.6375 X 10^5 to 1.2 X 10^5. A four, five and six bladed vertical axis vane typerotor was used to determine the aerodynamic properties in dynamic condition. It is found that the power coefficient increases with increasing the number of blade but the significant effect of even and odd number blade is observed on the range of tip speed ratio. An odd number bladed rotor covered a wide range of tip speed ratio compare to the even number one.